Do the Performance of Islamic Banking and Islamic Bonds (Sukuk) Influence Indonesia's Economic Growth? - Amijaya, Rachmania Nurul Fitri; Alfaroby, Sulthan Hakim Aviecenna; Putra, Perdana Nanda Hari; Adlani, Shofiyuddin Akmal (Institut Agama Islam Negeri Madura, 2024)
The influence of Islamic banking and Sharia bonds on the economic growth of Indonesia will be discussed in this article, considering the return on assets (ROA) and the development of sukuk in Indonesia. In this research, the return on assets of Islamic commercial banks and the cumulative value of sukuk issuances are the independent variables, while the gross domestic product is the dependent variable. A quantitative approach is used in conjunction with a multiple linear regression model. Secondary data used in this study is sourced from the Financial Services Authority (OJK) and the Central Statistics Agency (BPS). The data covers the first quarter of 2015 to the second quarter of 2023. The data is processed using Eviews 10 to analyze the Gross Domestic Product (GDP), Return on Asset (ROA), and Cumulative Value of Sukuk Issuance (NAP). The results indicate that the variable of cumulative sukuk issuance has a significant influence on economic growth, while the variable of return on assets of Islamic commercial banks does not have a significant influence on economic growth.